The Role of Performance Appraisal, Work Motivation, and Training Effectiveness on the Productivity of Sales Personnel in FMCG Companies - Endrawati, Titin; Nawiyah, Nawiyah (West Science Journal Economic and Entrepreneurship, 2025)
This study investigates the role of performance appraisal, work motivation, and training effectiveness in enhancing the productivity of sales personnel in Fast-Moving Consumer Goods (FMCG) companies in Indonesia. A quantitative approach was adopted, using a structured questionnaire to collect data from 305 sales personnel across various FMCG companies. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all three factors—performance appraisal, work motivation, and training effectiveness—positively influence the productivity of sales personnel. Among these, work motivation showed the strongest impact, followed by performance appraisal and training effectiveness. The results highlight the critical importance of integrating these factors into human resource management practices to improve sales performance. This study provides valuable insights for FMCG companies seeking to enhance the productivity of their sales teams through targeted performance management, motivational strategies, and training programs.